Phylogenetic Relationships Among Selected Heteroderoidea Based on 18S and ITS Ribosomal DNA - Ferris, V R (Journal of nematology, 2004)
In a study of relationships among selected cyst-forming and noncyst-forming species of Heteroderoidea, combined sequences comprised of DNA from part of the conserved 18S ribosomal RNA gene (rDNA) plus the complete ITS rDNA segment were more similar to analyses based on the ITS data alone than to analyses based on the 18S data alone. One of the two noncyst-forming species, Ekphymatodera thomasoni, grouped with cyst-forming species of Heteroderoidea. Bilobodera flexa, also a noncyst-forming species, was separated from all the other taxa by a long branch. Afenestrata koreana, with a weakly sclerotized cyst, grouped closely with H. bifenestra. These observations suggest that phylogenetic analyses using molecular data may aid in our understanding of the evolution of cyst formation in nematodes, including the possibility of secondary loss. The usefulness of molecular phylogenetic analyses in nematodes may depend more on the particular selection of taxa than on mere addition of data from additional genes